Ritual Kissing, Heresy and the Emergence of Early Christian Orthodoxy - Penn, Michael Philip (The journal of ecclesiastical history, 2003)
Amidst the theological controversies of the fourth and fifth centuries, the ritual kiss often played an important role in trying to distinguish orthodox from heretical Christians. For early Christian leaders such as Rufinus, Jerome, Augustine and Paulinus of Nola, the kiss became a means to malign an opponent while simultaneously reinforcing one's own claims to theological legitimacy. The kiss's connection to a wide range of symbolic systems made it a particularly versatile tool for early Christian polemics.